THE EVOLUTION OF THE ECONOMY BETWEEN 2006 - 2021 MEASURED BY GDP, GDP PPP IN ACCORDANCE WITH THE AVERAGE WAGES - EURO AREA VS ROMANIA – - CSŐSZ CSONGOR (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
The economic growth, the economic situation of a country is a significant theme in economic literature. In this article we analyze the change in GDP per capita euro area 2006 - 2021, GDP per capita Romania 2006 - 2021, GDP PPP per capita euro area 2006 - 2021, GDP PPP per capita Romania 2006 - 2021, average monthly wages in the euro area 2006 - 2021, average monthly wages in Romania 2006 – 2021, ratio of the GDP PPP per capita Romania and the euro area, average monthly wages ratio Romania and the euro area and hourly labor cost related to the 2008 – 2021 period, to formulate a conclusion about this modifications. The conclusion will be formulated based on validated and/or invalidated hypotheses. We want to find the answer to the statement: economic development measured by GDP, GDP PPP is accordance with the average monthly wages earned by employees in Romania compared to the countries of the euro area (19 countries).